1)   Vypočtěte:

\displaystyle 15-16=

\displaystyle -3+\left( -6 \right)=

\displaystyle 2-\left( -5 \right)=

\displaystyle 17-\left( +2 \right)=

\displaystyle 39-\left( -42 \right)=

\displaystyle -5-\left( -6 \right)=

\displaystyle 12-15=

\displaystyle -7+\left( -8 \right)=

\displaystyle -11+2=

\displaystyle -1-\left( -4 \right)=

\displaystyle -2+\left( -9 \right)=

\displaystyle 3-\left( +6 \right)=

\displaystyle 11-\left( +12 \right)=

\displaystyle +5+\left( -15 \right)=

\displaystyle +12+\left( -16 \right)=

\displaystyle -3-\left( -8 \right)=

 

2)   Vypočtěte:

\displaystyle -1-15=

\displaystyle -9-\left( -3 \right)=

\displaystyle -7-\left( -2 \right)=

\displaystyle 5+\left( -17 \right)=

\displaystyle 15-\left( +16 \right)=

\displaystyle 1-\left( -5 \right)=

\displaystyle -27-\left( -12 \right)=

\displaystyle -15-\left( -7 \right)=

\displaystyle -9-\left( -11 \right)=

\displaystyle -2+\left( -15 \right)=

\displaystyle 3-\left( -1 \right)=

\displaystyle -11+\left( -2 \right)=

\displaystyle -3+\left( -3 \right)=

\displaystyle -1+\left( -11 \right)=

\displaystyle 30-\left( +23 \right)=

\displaystyle -98-2=

\displaystyle 12+\left( -5 \right)=

\displaystyle -1+\left( -3 \right)=

\displaystyle 20-\left( +16 \right)=

\displaystyle 21-\left( -22 \right)=